Irrational rationales: vicarious and fictional justifications among ideological killers - Langman, Peter (International journal of comparative and applied criminal justice, 2024)
This article explores the motivations of ideological killers by investigating their justifications for violence. These justifications are divided into three categories: those that are grounded in actual social/political realities that are present in the lives of the perpetrators; those that utilise geographically and/or temporally distant vicarious victimisations; and those that are fictional, i.e., they have no basis in reality. These concepts are illustrated through discussions of a range of perpetrators of ideological violence. The implications of vicarious and fictional motivations are discussed in terms of our understanding of the psychology of perpetrators, the process of radicalisation, and counterterrorism efforts.